The Role of Emotional Intelligence to Teacher Perception of Student- Teacher Relationships - Saleh, Airin Yustikarini; Hibatullah, Mario Djabbar Aidil (Jurnal Pendidikan Progresif, 2023)
The Role of Emotional Intelligence to Teacher Perception of Student-Teacher Relationship. A positive relationship between teachers and students is affected by many factors. Teacher competency in evaluate emotion of oneself and others, and regulating their emotion will have impact on their perception of relationship with students. Based on previous studies, the study on how teacher's emotional intelligence relates to teacher-student relationships has not received much attention. Objectives: This study aims to investigate the relationship between teacher emotional intelligence and teacher perception regarding their relationship with students. Methods: This study uses a cross-sectional design with simple linear regression analysis was used to measure the effect of emotional intelligence to teacher-student relationships. Teacher emotional intelligence was measured using Schutte’s Emotional Intelligence Scale (SEIS), while student-teacher relationship was measured using Student-Teacher Relationship Scale (STRS). Findings: Linear regression analysis from 1420 participants showed that there is significant effect of teacher emotional intelligence to student-teacher relationship. Conclusion: The implication of this research is developing and maintaining teacher emotional intelligence is importance because have impact in their relationship with students. Keywords: emotional intelligence, teacher-student relationship, teacher emotion, teacher and student.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202350